PRINCIPLES OF LIQUID PRESSURE EFFECT ON THE COCOON SHELL (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In this work, the force of the hydrostatic pressure of the liquid on the shell of the cocoon during the steaming of the cocoon in a universal vacuum cocoon steamer is theoretically studied. Since the cocoon consists of a curved surface, the effect of fluid pressure on the curved surfaces is also determined. Equations are also presented for finding the pressure force itself through the horizontal and vertical components of the pressure applied to a curved surface.